Shape and Height of Human Duodenal Villi - Sayeed, Sharmina; Ara, Shamim; Reza, Rumana; Rahman, Sadia; Kashem, Kanetarin; Paul, Uttam Kumar (Bangladesh Journal of Anatomy, 2015)
Context: Villus atrophy of the small intestine is one of the causes of chronic diarrhoea. The etiology of villus atrophy of the small intestine includes celiac disease, tropical sprue, Giardiasis etc. The knowledge of villus shape and height of duodenum in Bangladeshi people can help the gastroenterologist to diagnosis and provide better treatment. Materials & Methods: A Cross sectional, analytical type of study was performed in the Department of Anatomy of Dhaka Medical College, Dhaka from July 2010 to June 2011 on histological slides of 19 human duodenums of Bangladeshi people. The sample was divided into 5 different age groups, group A (20-29 years), group B (30-39 years), group C (40-49 years), group D (50-59 years) and group E (60-69 years). From group A, B and C five duodenums and from group D and E two duodenums were stained with Harris’ Haematoxylin and Eosin stains. From each four parts of duodenum four paraffin blocks were prepared and best 76 slides were taken. The shape of villi in each four parts of the duodenum was observed and noted. The height of villi was measured by using a stage micrometer and ocular micrometer. Results: The shape of the villi were broader & shorter in age group E (60-69 years). Villi were found finger sharped in all age groups. The mean difference in height of villi in different parts of duodenum between group A and B, group B and C, group B and D, group C and D, group C and E, group D and E were statistically not significant. But the difference between height of villi of the first part of the duodenum in group A and C, group A and D, group A and E, group B and E found statistically significant (p< 0.05) and the difference between height of villi of fourth part of the duodenum in group A and C, group A and D, group A and E found statistically significant (p < 0.05). Bangladesh J. Anat. 2015; 13(1) : 1-7